Elements that influenced immediate mother-neonate contact during the golden hour* - Monteiro, Bruna Rodrigues; Silva, Valéria Gomes Fernandes da; Andrade, Anny Suelen dos Santo; Machado, Luciara Silva; Pinto, Erika Simone Galvão; Souza, Nilba Lima de (Revista da Escola de Enfermagem da USP, 2022)
Objective: To characterize the elements that influenced the immediate mother-neonate contact during the golden hour. Method: A cross-sectional observational study with a quantitative approach. A total of 105 parturient women hospitalized in two maternity hospitals with usual risk were observed. The instrument was based on Brazilian National Normal Childbirth Care Guidelines and World Health Organization good obstetric practices, totaling 36 questions. The analysis took place in a descriptive way using the Chi-Square Test for proportion comparison. Results: Of the parturient women, 2.8% (n = 3) experienced the golden hour, and 82.9% (n = 87), immediate contact between 1 and 5 minutes. In 85.7% (n = 90) of the group, there were no causes that contraindicated immediate contact. For 48.0% (n = 49) of participants, contact was re-established by the nursing staff within 31–60 minutes. Conclusion: Immediate contact during the golden hour had low hospital care compliance. Neonatal procedures that can be postponed predominated as influencing elements of the golden hour. The assistance observed in the birth rooms investigated reflects the need to reduce interventions in labor and birth.